Disaster readiness of the College of Arts and Letters library, University of the Philippines, Diliman - Belmonte, Abel A.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
Disasters are occurrences that cause destruction of property and livelihood at the afflicted area. Disasters have been a problem for libraries, and so disaster plans are made for libraries to be able to face and handle incoming disasters while having minimal loses. However, many libraries have neither disaster plans nor guidelines in making a disaster plan. Such is the case of the College of Arts and Letters Library (CAL Library). This study aims to create a set of guidelines to help the library make its own disaster plan.
This study made an on-site observation, gathering data from the external environment of the CAL Library like the elevation and vegetation of surrounding are, as well as the internal environment like the positions of fire exits, the structure of the library, and the equipment. During the on-site observation, the researcher then used a checklist based on the IFLA disaster plan manual to see whether the library complied with the standards and guidelines given in the manual. Questionnaires were given to the staff and to the head librarian to receive answers regarding disaster plan and its aspects.
The data gathered from the on-site observation revealed that the CAL Library was in a disaster-prone area. The CAL Library was situated in the first floor of the CAL Building, in the lowest elevation from a slope and is surrounded with high elevated land. The wall of the library had cracks and faded paint, patched floors, but had emergency exists. From the questionnaires, it was gathered that only a few of the staff members had been trained to face and handle disasters, and that there was no budget allotted for disaster management.
With those data gathered in mind, it is concluded that the CAL Library only had the most basic measures when facing and handling a disaster. There was in need of a more adequate disaster plan so that many of the deficiencies would be alleviated.
Recommendations included the set of guidelines created for the CAL Library. The guidelines serve only as a draft or an outline of what disaster plan the library should come up with. It used the data gathered in constructing the set of guidelines, each sorted to the four stages found in a disaster plan. Other recommendations given were the IFLA disaster plan manual, which served as the basis for the checklist, as well as the undergraduate theses that helped other institutions in making a disaster plan.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) College of Arts and Letters Library; Emergency management -- Philippines -- Quezon City